Robotics in Education Research and Practices for Robotics in STEM Education - Merdan, Munir; Lepuschitz, Wilfried; Koppensteiner, Gottfried; Balogh, Richard; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This proceedings volume showcases the latest achievements in research and development in Educational Robotics presented at the 7th International Conference on Robotics in Education (RiE) held in Vienna, Austria, during April 14-15, 2016. The book offers a range of methodologies for teaching robotics and presents various educational robotics curricula. It includes dedicated chapters for the design and analysis of learning environments as well as evaluation means for measuring the impact of robotics on the students' learning success. Moreover, the book presents interesting programming approaches as well as new applications, the latest tools, systems and components for using robotics. The presented applications cover the whole educative range, from elementary school to high school, college, university and beyond, for continuing education and possibly outreach and workforce development. The book provides a framework involving two complementary kinds of contributions: on the one hand ontechnical aspects and on the other hand on matters of didactic. .
Didactic and Methodologies for Teaching Robotics -- Educational Robotics Curricula -- Design and Analysis of Learning Environments -- Technologies for Educational Robotics -- Measuring the Impact of Robotics on Students' Learning.
Keywords: Computational intelligence; Control engineering; Robotics; Automation; Artificial intelligence; Computational Intelligence; Control, Robotics, Automation; Artificial Intelligence